An Actual Insight into the Pathogenic Pathways of Ankylosing Spondylitis - Emilia-Daniela Păsăran; Andreea Elena Diaconu; Corina Oancea; Andra-Rodica Bălănescu; Sorina Maria Aurelian; Corina Homentcovschi (Current Issues in Molecular Biology, 2024)
Spondyloarthritis refers to a broad group of conditions that include ankylosing spondylitis, psoriatic arthritis, reactive arthritis, and enteropathic arthritis associated with Crohn’s disease or ulcerative colitis. They have been classified by the ASAS group (ASsessment in Ankylosing Spondylitis) into axial spondyloarthritis and peripheral spondyloarthritis. Common features include the absence of autoantibodies, genetic predisposition, and clinical aspects such as axial joint involvement, peripheral manifestations, and extra-articular involvement. However, the pathogenic mechanisms remain complex and incompletely elucidated, despite the fact that the specialized literature has described several pathways that act in synergy: genetic predisposition, environmental factors (infections and mechanical stress), or innate and acquired immune mechanisms. Finally, an inflammatory response is triggered by the recruitment of a large number of inflammatory cells and the release of innate cytokines in the affected areas: joints or periarticular or extraarticular tissues. The current article aims to update and systematize the knowledge accumulated so far on this topic, focusing on the mechanisms that have been involved in the onset, progression, and severity of ankylosing spondylitis.